2010
DOI: 10.1021/jp912052u
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Silicon Nanocrystal Surfaces Exposed to Ammonia

Abstract: Silicon nanocrystals (NCs) 8-10 nm in diameter are grown on SiO 2 surfaces in an ultrahigh-vacuum chamber using hot wire chemical vapor deposition. These NCs are subjected to varying exposures of deuterated ammonia (ND 3 ). The surface chemistry of Si NCs is studied using X-ray photoelectron (XP) spectroscopy and temperature-programmed desorption (TPD). The dissociative adsorption of ND 3 on Si NCs results in the formation of ND 2 species prior to TPD, and Si 3 N (nitride) formation is observed after TPD. D 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Without being embedded in a matrix, freestanding Si NCs have gained popularity owing to their easily accessible surface. 2,[11][12][13][14][15][16][17] Both ammonia exposure of as-synthesized Si NCs 16 and intentional nitrogen doping during Si NC synthesis 17 have attempted to improve the stability of freestanding Si NCs in air.…”
mentioning
confidence: 99%
“…Without being embedded in a matrix, freestanding Si NCs have gained popularity owing to their easily accessible surface. 2,[11][12][13][14][15][16][17] Both ammonia exposure of as-synthesized Si NCs 16 and intentional nitrogen doping during Si NC synthesis 17 have attempted to improve the stability of freestanding Si NCs in air.…”
mentioning
confidence: 99%
“…As shown in Figure 8, these particles acquire a polymer coating of only about 4 nm which is less than the one of silica agglomerates. The dissociative adsorption of ammonia on silica surfaces has been studied using X-ray photoelectron spectroscopy (XPS) and temperature-programmed desorption (TPD) (Taylor et al 1989;Salivati et al 2010). It was found that the dissociative adsorption of ammonia on Si (100) at 300 K leads to the formation of NH 2 (a) and H(a) species.…”
Section: Influence Of Particle Sizementioning
confidence: 99%
“…The mono- and dideuteride are denoted by β 1 and β 2 , which desorb around 780 and 680 K, respectively; the trideuteride denoted by β 3 appears as a broad low temperature feature before the dideuteride feature. In the N 1s XP spectra, the Si−ND 2 species appear at 398.5 eV and the Si 2 ND species appear at 398 eV . ND 3 exposures are reported in Langmuirs (1 L = 10 −6 Torr s).…”
mentioning
confidence: 96%
“…Umemoto et al have shown that ammonia decomposition on a hot tungsten filament results in the formation of predominantly H atoms and NH 2 radicals, with NH radicals formed as a minor product . In separate experiments, a hot tungsten filament was used to predissociate ND 3 before adsorption on the NC surface . XP spectra revealed that Si−ND 2 species are present initially, but as the ND 3 dose is increased, Si 2 ND species dominate.…”
mentioning
confidence: 99%
See 1 more Smart Citation